Country-by-Country Reporting: The pros and cons of more tax transparency - Tobias Hentze (Institut der deutschen Wirtschaft (IW), 2016)
The European Commission will present its proposal for more corporate tax transparency these days. The so-called Country-by-Country Reporting will force large multinational enterprises to publish country specific profits and tax payments. By emphasizing positive aspects such as disclosing the tax contributions of global corporations, the European Commission forgets to look at the increasing red tape burden for companies and to address tax loopholes established by the national governments in the EU member states. It also risks competitive disadvantages and reputational damage for MNE by publishing sensitive company data.
Keywords: 330